Varied female and male courtship behavior facilitated the evolution of a novel sexual signal. (8th June 2022) - Fitzgerald, Sophia L; Anner, Sophia C; Tinghitella, Robin M
Abstract: Sexual selection can contribute to speciation when signals and preferences expressed during mate choice are coupled within groups, but come to differ across groups (generating assortative mating). When new sexual signals evolve, it is important to investigate their roles in both mate location and courtship contexts, as both signaling functions are critical in mate choice. In previous work, researchers identified two new male morphs (silent and purring) in Hawaiian populations of the Pacific field cricket, Teleogryllus oceanicus. These morphs likely evolved because they protect males from an acoustically orienting parasitoid, yet still obtain some reproductive success. But, it remains unknown how the purring morph functions in close courtship encounters. We compared the relative success of the very recently evolved purring morph to that of the ancestral and silent morphs during courtship encounters. Purring males produce a novel courtship song and were not as successful in courtship as the ancestral type, but were mounted by females as often and as quickly as the obligately silent morph that arose and spread ~20 years ago. Purring males initiate courtship more quickly than other morphs, and females from populations where purring is common exhibit higher overall mounting rates. Thus, differences in the behavior of purring males and of females from populations where purring is common may have facilitated the origin of this novel sexual signal. We found no assortative mating between males of a given morph and females from their own population, and so we hypothesize that multiple male types will be maintained within the species because each achieves fitness in different ways. Abstract : Female crickets choose their mates by assessing the songs of courting males. But what happens when different evolutionary pressures change those songs? Will females still accept them? We studied how two newly evolved male cricket types that do not make the typical song, but are protected from a deadly fly, fare in courtship. Turns out that less desirable males still have a shot at passing on their genes if the females they court are less picky.